Specific Far Infrared Spectroscopic Properties of Phospholipids - Hielscher, Ruth; Hellwig, Petra (Spectroscopy: An International Journal, 2012)
We describe the specific spectral signature of different phospholipids and sphingolipids in the far infrared. Three specific spectral domains have been found: the head group contributions (600 and 480 cm−1); the modes of the torsion motion of the hydrocarbon chains and of the skeleton vibration (460 to 180 cm−1); and the hydrogen-bonding continuum (below 300 cm−1). Marker bands for individual phospholipids are distinguished.